ANTIMICROBIAL RESISTANCE CARRIAGE AMONG EMERGENCY AND IN-HOSPITAL PATIENTS IN BENIN CITY, NIGERIA - Elimian, Kelly; Ibadin, Ephraim (FUDMA Journal of Sciences, 2026)
Antimicrobial resistance (AMR) is an escalating threat in sub-Saharan Africa, where hospital-based paediatric data remain limited. This study assessed the prevalence, distribution, and resistance patterns of microorganisms among children receiving care at a tertiary hospital in Benin City, Nigeria. This was a hospital-based cross-sectional analysis of paediatric patients with linked clinical and microbiological data at the University of Benin Teaching Hospital. Antimicrobial susceptibility testing was performed using the Kirby–Bauer disc diffusion method and interpreted according to Clinical and Laboratory Standards Institute criteria. Resistance phenotypes included methicillin-resistant Staphylococcus aureus (S. aureus; MRSA), extended-spectrum beta-lactamase (ESBL) production, carbapenemase production, and multidrug resistance (MDR; resistance to ≥3 antimicrobial classes). The primary outcome was any AMR at the patient level. Among 44 unique patients, AMR was detected in 12 (27.3%; 95% CI, 15.0–42.8). A total of 70 isolates were identified, dominated by S. aureus (50.0%) and Enterobacterales (25.7%). MRSA accounted for 20.0% of S. aureus isolates. Among Enterobacterales, 38.9% were ESBL-producing, and 38.9% were identified as carbapenemase-producing. Antibiotic-specific resistance was highest for trimethoprim–sulfamethoxazole (100%), nitrofurantoin (63.6%), and ciprofloxacin (54.5%), whereas phenotypic carbapenem resistance was low. AMR was strongly associated with emergency presentation (100.0% vs. 6.5% in non-emergency settings; p
Keywords: Antimicrobial resistance; Paediatric population; Methicillin-resistant Staphylococcus aureus; Extended-spectrum beta-lactamase; Carbapenemase-producing Enterobacterales; Nigeria